l-Fucose-containing arabinogalactan-protein in radish leaves - Inaba, Miho (Carbohydr Res, 2015)
The carbohydrate moieties of arabinogalactan-proteins (AGPs) have β-(1→3)-galactan backbones to which side chains of (1→6)-linked β-Gal residues are attached through O-6. Some of these side chains are further substituted with other sugars. We investigated the structure of l-Fuc-containing oligosaccharides released from the carbohydrate moieties of a radish leaf AGP by digestion with α-l-arabinofuranosidase, followed by exo-β-(1→3)-galactanase. We detected a series of neutral β-(1→6)-galactooligosaccharides branching variously at O-3 of the Gal residues, together with corresponding acidic derivatives terminating in 4-O-methyl-GlcA (4-Me-GlcA) or GlcA at the non-reducing terminals. In neutral oligosaccharides with degree of polymerization (dp) mainly higher than 10, l-Fuc groups were attached through l-Ara residues as the sequence, α-l-Fucp-(1→2)-α-l-Araf-(1→. This sequence was verified by isolation of the pentasaccharide α-l-Fuc-(1→2)-α-l-Araf-(1→3)-β-Gal-(1→6)-β-Gal-(1→6)-Gal upon digestion of the higher oligosaccharides with endo-β-(1→6)-galactanase. By contrast, in lower polymerized (predominantly dp 4) acidic oligosaccharides, l-Fuc groups were attached directly at the non-reducing terminals through α-(1→2)-linkages, resulting in the release of the tetrasaccharides, α-l-Fucp-(1→2)-β-GlcA-(1→6)-β-Gal-(1→6)-Gal and α-l-Fucp-(1→2)-β-4-Me-GlcA-(1→6)-β-Gal-(1→6)-Gal. In long acidic oligosaccharides with dp mainly higher than 13, l-Fuc groups localized on branches were attached to the uronic acids directly and/or l-Ara residues as in the neutral oligosaccharides.